S Sustainable Viability for Restoration and Adaptive Reuse of Sikh Era Havelis in Lahore, Pakistan - Dr Sadia Farooq; Amna Khalid Qureshi (Sir Syed University Research Journal of Engineering and Technology, 2020)
This research is concept based investigation of assessing the practical viability in terms of sustainability, for restoration and adaptive reuse of Sikh Era historic Havelis in Lahore. The timeless history, architecture and unique features of interior built environment of Sikh Era havelis are considered to be as an ideal aspiration for conservation and adaptive reuse in the recent times. History reveals that there are several examples of reused historic buildings that illustrate the practicality of the concept in terms of sustainability; economic impact, vitality of social life, and usability of existing urban resources including energy saving. A heritage survey of Sikh Havelis in Lahore, expert interviews and a review of literature concerning adaptive reuse of historic buildings is used as a tool of conducting qualitative and comparative research. The research recommends key implications for local governments in Lahore and eventually provide a theoretical research framework that can be incorporated in the decision-making processes for adaptive reuse projects. The expert opinion directs that adaptive reuse is important for quality enhancement, practicing sustainability principles, renew the old resource with future demands. The experts were agreed that adaptive reuse increases the age of building, provides safe and healthy environment and feasibility stage of adaptive reuse give direction to decision process.